Diagnosis and intervention of severe tricuspid regurgitation secondary to rupture of the chordae tendineae: A case report and literature review - Huang, Jiaxi; Du, Chaojun; Zhang, Wenbo; Mi, Yaping; Shan, Yaping; Zhang, Huifeng; Shi, Qiqi; Chen, Gang (Frontiers in Pediatrics, 2023)
Unguarded severe tricuspid regurgitation (TR) caused by rupture of papillary muscle or chordae tendineae is rare but fatal in neonates. The experience of management of these patients is still limited. A newborn presenting severe cyanosis after delivery was diagnosed with severe tricuspid regurgitation secondary to rupture of chordae tendineae by Echocardiography (Echo), then treated by surgical reconstruction of chordae/papillary muscle connection without artificial materials. A take-away lesson from this case is that Echo is an important method to diagnose rupture of chordae tendineae or papillary muscle, and that prompt diagnosis and timely surgery can be life-saving.